Role clarity, autonomy, work engagement and voluntary turnover intentions: the moderating role of personal circumstances - Syed Abu Bakar, Syarifah Mastura; Tara Singh, Harpajan Singh; Salahudin, Shahrul Nizam; Al Qershi, Nagwan; Saad, Abidah; Sandhu, Sukjeet (2021)
The main objective of this study was to examine the relationship between the role clarity, autonomy, work engagement, personal circumstances and voluntary turnover intentions. Data were collected from 322 employees of an Information and Communication technology industry in Malaysia. A partial least square structural equation modelling approach was used to analyze the data. The results showed a significant relationship was found between role clarity, autonomy and work engagement predict the voluntary turnover intentions, with personal circumstances moderating the relationship. The findings from the study will help to develop further theory and managerial understanding on issues relating to voluntary turnover intentions.